Acquisition of multiple photon pairs with an EMCCD camera. (18th April 2017) - Bolduc, Eliot; Faccio, Daniele; Leach, Jonathan
Abstract: The detection and characterization of quantum states of light plays an important role in quantum science. Traditional methods use single-photon detectors, but these are generally limited to point measurements; consequently, multi-pixel devices are now being utilized in quantum measurements, especially in the field of quantum imaging. Here, we demonstrate the capability of an EMCCD camera to record multiple coincidence events originating from parametric downconversion where the mean photon number per pixel is much greater than unity. The multi-pixel nature of the camera enables us to record correlations ranging from ≈ 1 to 10 000 coincidences per frame. This approach to quantum measurements provide mechanisms for recording quantum signatures for bright correlated photon sources.